Innovativeness of Polish enterprises in the initial period of system transformation - Baruk, Jerzy
The author examines innovativeness in Polish industry since the transformation of its economy to a market-based one. It appears that the changes commenced in 1989 did not influence innovation in any evident way.
Since 1989, the Polish economy has been transformed to a market economy. Innovations are one of the key instruments of system change and economic development. The main aim of this article is to find the answer to the question of to what degree the system changes implemented in the Polish economy have influenced an increase of innovativeness in enterprises. These considerations are based on the results of a research questionnaire on the innovativeness of Polish industry, carried out by the Central Statistical Office of Poland among 2430 firms belonging to both the public and the private sector. For this analysis, the enterprises were divided according to which sector they belonged to and then into four groups labelled small, middle-sized, large and very large. The research did not confirm the current opinion that the innovativeness of the private sector was bigger than that of the public sector, because in fact the innovative activity of the public sector was larger. Nor was there any confirmation of the opinion that small enterprises showed larger innovativeness. It may be stated that the system changes started in 1989 did not influence the increase in innovativeness of Polish enterprises in any explicit way.
Keywords: Innovativeness; Polish enterprises; System transformation